Stachyose Alleviates Corticosterone-Induced Long-Term Potentiation Impairment via the Gut–Brain Axis - Huang, Yan; Li, Dong; Wang, Chen; Sun, Na; Zhou, Wen-Xia (Frontiers in Pharmacology, 2022)
Stress can induce learning and memory impairment; corticosterone is often used to study the effects and mechanisms of stress in animal models. Long-term potentiation (LTP) has been widely used for tackling the mechanisms of memory. Liuwei Dihuang decoction-active fraction combination (LW-AFC) can improve stress induced LTP and cognition impairment, stachyose is an oligosaccharide in LW-AFC. The effects and mechanisms of stachyose on stress are unknown. In this study, stachyose had protective effects against LTP impairment by corticosterone in vivo only via intragastric administration for 7 consecutive days, but there was little effect even injection directly into the intracerebroventricular; the protective effect of stachyose could be cancelled by non-absorbable antibiotics (ATB) which disturbed gut flora. 16S rRNA sequencing, alpha diversity and Principal coordinate analysis (PCoA) revealed the gut flora in corticosterone-treated mice was disturbed and stachyose could improve corticosterone induced gut flora disturbance; Bacteroidetes decreased and Deferribacteres increased significantly in corticosterone-treated mice, stachyose restored Bacteroidetes and Deferribacteres to the normal level. D-serine, a coactivator of NMDA receptors, plays an important role in synaptic plasticity and cognition. Here, corticosterone had little effect on the content of D-serine and L-serine (the precursor of D-serine), but reduced the D-serine release related proteins Na+-independent alanine–serine–cysteine transporter-1 (ASC-1) and vesicle-associated membrane protein 2 (VAMP2) significantly in hippocampus; stachyose significantly increased ASC-1 and VAMP2 in corticosterone-treated mice, and ATB blocked stachyose’s effects on ASC-1 and VAMP2. NMDA receptors co-agonists L-serine, D-serine and glycine significantly improved LTP impairment by corticosterone. These results indicated that Stachyose might indirectly increase D-serine release through the gut-brain axis to improve LTP impairment by corticosterone in the hippocampus in vivo.